Emotional Intelligence and Academic Performance of Students: Exploring Sustainable Higher Education - Shrestha, Bibek (Academia Journal of Humanities & Social Sciences, 2025)
Emotional Intelligence (EI) has emerged as a critical factor influencing professional success and personal development. In the case of this study, the paper studies the relationship between EI and academic performance among students from three colleges in Pokhara: Informatics College Pokhara (ICP), LA Grandee International College, and Pokhara College of Management (PCM). Using the Schutte Self-Report EI Test (SSEIT) to evaluate EI across the variables like self-awareness, self-regulation, motivation, and empathy, the study categorizes students into high EI, average EI, and needs improvement. Academic performance is assessed through self-reported GPA/marks in their last semester. The findings of the study revealed a positive relation between EI and academic outcomes, suggesting that integrating EI development into academic curriculum can significantly enhances students' academic success and overall well-being. Additionally, the study highlights that students with higher EI scores not only perform better academically but also exhibit superior stress management and interpersonal skills. By focusing on self-regulation and motivation, which emerged as the key indicators of academic performance, the study underscores the transformative potential of EI in the educational contexts. These findings align with the global research trends, emphasizing the need for the comprehensive EI-based interventions to address the academic and emotional challenges faced by students in Nepal. The study also highlights the importance of fostering EI in the younger generations, preparing them for both academic and professional challenges. It offers the practical insights into integrating the EI frameworks into the education system, aiming to bridge the gap between academic potential and emotional competence for a holistic student success, contributing to sustainable higher education in Nepal. Additionally, this study applies a developmental perspective, highlighting how EI evolves over time due to age.